‘I never feel alone in my classroom’: teacher professional growth within a blended community of practice - Trust, Torrey; Horrocks, Brian (Professional Development in Education, 2017)
Well-designed face-to-face and virtual communities of practice provide opportunities for teachers to learn, grow as professionals and make changes to their practice with the support of peers. However, as more K–12 teachers become Connected Educators and act as conduits between online spaces and communities in their schools, the boundaries between face-to-face and online communities of practice are blurred. While increasingly more teachers are engaging in blended learning opportunities, there is a dearth of research about how blended communities of practice shape K–12 teachers’ learning and professional growth. This manuscript reports the findings of a qualitative study that examined teachers’ experiences in a blended community of practice through in-depth interviews with 26 K–12 teachers. Data analysis suggests that multiple means of engagement, face-to-face learning activities and leadership roles are critical elements that shape participation and learning in a blended community of practice. Additionally, participation in a blended community of practice creates reciprocal growth opportunities, in which teachers can develop as professionals across multiple domains (e.g. individual, classroom, school, blended community of practice), while also shaping the growth of these domains. These findings have implications for shaping the future development and research of teacher learning in blended communities of practice.
Keywords: blended learning; community of practice; discovery educator network; professional development; teacher learning